Facing the "new normal": How adjusting to the easing of COVID-19 lockdown restrictions exposes mental health inequalities. (September 2021) - Fineberg, Naomi A.; Pellegrini, Luca; Wellsted, David; Hall, Natalie; Corazza, Ornella; Giorgetti, Valentina; Cicconcelli, Dorotea; Theofanous, Elena; Sireau, Nick; Adam, David; Chamberlain, Samuel R.; Laws, Keith R.
Abstract: Background: Re-establishing societal norms in the wake of the COVID-19 pandemic will be important for restoring public mental health and psychosocial wellbeing as well as economic recovery. We investigated the impact on post-pandemic adjustment of a history of mental disorder, with particular reference to obsessive-compulsive (OC) symptoms or traits. Methods: The study was pre-registered (Open Science Framework; https://osf.io/gs8j2/ ). Adult members of the public (n = 514) were surveyed between July and November 2020, to identify the extent to which they reported difficulties re-adjusting as lockdown conditions eased. All were assessed using validated scales to determine which demographic and mental health-related factors impacted adjustment. An exploratory analysis of a subgroup on an objective online test of cognitive inflexibility was also performed. Results: Adjustment was related to a history of mental disorder and the presence of OC symptoms and traits, all acting indirectly and statistically-mediated via depression, anxiety and stress; and in the case of OC symptoms, also via COVID-related anxiety (all p < 0.001). One hundred and twenty-eight (25%) participants reported significant adjustment difficulties and were compared with those self-identifying as "good adjusters" (n = 231). This comparison revealed over-representation of those with a history or family history of mental disorder in the poor adjustment category (all p < 0.05). 'Poor-adjusters' additionally reported higher COVID-related anxiety, depression, anxiety and stress and OC symptoms and traits (all p < 0.05). Furthermore, history of mental disorder directly statistically mediated adjustment status (p < 0.01), whereas OC symptoms (not OC traits) acted indirectly via COVID-related anxiety (p < 0.001). Poor-adjusters also showed evidence of greater cognitive inflexibility on the intra-extra-dimensional set-shift task. Conclusion: Individuals with a history of mental disorder, OC symptoms and OC traits experienced greater difficulties adjusting after lockdown-release, largely statistically mediated by increased depression, anxiety, including COVID-related anxiety, and stress. The implications for clinical and public health policies and interventions are discussed. Highlights: A quarter of a sample of the public surveyed reports difficulties adjusting to lockdown-release. Those with a history of mental disorder are disproportionately affected. Obsessive compulsive symptoms or traits and cognitive inflexibility also predict poor adjustment. Difficulty adjusting after lockdown-release is mediated by depression, anxiety and stress. People with mental disorders will need help in re-adjusting when the COVID-19 pandemic ends.